The 2nd International Electronic Conference on Foods—“Future Foods and Food Technologies for a Sustainable 2021
DOI: 10.3390/foods2021-11066
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Capsaicin, Dihydrocapsaicin and Phenolic Content in Habanero Chillies

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Polyphenol contents in peppers were been reported in other studies [14,38], which indicated that the potential for polyphenols in hybrids is more significant than in this study. It was reported in previous studies that there is a correlation between capsaicin and polyphenol content [37]. These compounds are spread throughout all parts of the plant as protectors against biotic and abiotic stresses [42].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Polyphenol contents in peppers were been reported in other studies [14,38], which indicated that the potential for polyphenols in hybrids is more significant than in this study. It was reported in previous studies that there is a correlation between capsaicin and polyphenol content [37]. These compounds are spread throughout all parts of the plant as protectors against biotic and abiotic stresses [42].…”
Section: Discussionmentioning
confidence: 96%
“…In addition to capsaicin, chili produces other functional secondary metabolites that can be developed industrially as functional foods, cosmetics, and pharmaceuticals [33]. Capsaicin is associated with beneficial biological effects in humans, including antioxidant activity [34][35][36], polyphenolic compounds [37,38], and even alpha-glucosidase inhibitory activity [35]. C. annuum L. species are reported to contain capsiate which can increase triglyceride accumulation, hepatic insulin sensitivity, and glycogen storage [39].…”
Section: Discussionmentioning
confidence: 99%